Influence of Mechanically Treating Recycled Aggregates on Concrete Strength - Ashraf H. Abdalkader; Mohammed A. Ali (African Journal of Advanced Pure and Applied Sciences, 2025)
Several studies have highlighted the potential of using recycled concrete aggregates (RCA) as a substitute for natural aggregates in concrete production due to their economic and environmental benefits. However, RCA generally exhibits lower engineering performance than natural aggregates, primarily because of its high water absorption. To address this limitation, researchers have explored various pretreatment methods, including thermal, mechanical, and chemical techniques. This study focused on investigating the impact of mechanical treatment of RCA on the compressive strength, indirect tensile strength, and workability of concrete, where natural coarse aggregates (10-20 mm) were partially replaced with RCA at proportions of 0%, 20%, 30%, 40%, 50%, and 60% by weight. The results showed that incorporating RCA tends to reduce both compressive and tensile strengths of concrete mixes, but this negative effect can be mitigated through mechanical treatment of the aggregates. Overall, mechanical pretreatment proves to be an effective approach to enhance the performance of RCA-based concrete, supporting its broader use as a sustainable alternative in construction.